2015
DOI: 10.1161/circheartfailure.113.001066
|View full text |Cite
|
Sign up to set email alerts
|

First Report on an Inotropic Peptide Activating Tetrodotoxin-Sensitive, “Neuronal” Sodium Currents in the Heart

Abstract: Background-New therapeutic approaches to improve cardiac contractility without severe risk would improve the management of acute heart failure. Increasing systolic sodium influx can increase cardiac contractility, but most sodium channel activators have proarrhythmic effects that limit their clinical use. Here, we report the cardiac effects of a novel positive inotropic peptide isolated from the toxin of the Black Judean scorpion that activates neuronal tetrodotoxinsensitive sodium channels. Methods and Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Previous studies have reported ZD7288 as a potent blocker of Nav1.4 (Wu et al Wu et al 2012 ) and in higher concentrations (> 100 µM) of low-voltage-activated calcium channels (Felix et al 2003 ; Sánchez-Alonso et al 2008 ), thereby characterizing this drug as a non-selective blocker for HCN channels. Considering that Nav1.4 channels are not present in rodent thalamic neurons (Kirchhof et al 2015 ) and based on the fact that we applied 10 µM ZD7288 (thus having little effect on low-voltage-activated calcium channels), the reduction of tonic firing of TC neurons seems to be mainly based on the block of HCN channels.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported ZD7288 as a potent blocker of Nav1.4 (Wu et al Wu et al 2012 ) and in higher concentrations (> 100 µM) of low-voltage-activated calcium channels (Felix et al 2003 ; Sánchez-Alonso et al 2008 ), thereby characterizing this drug as a non-selective blocker for HCN channels. Considering that Nav1.4 channels are not present in rodent thalamic neurons (Kirchhof et al 2015 ) and based on the fact that we applied 10 µM ZD7288 (thus having little effect on low-voltage-activated calcium channels), the reduction of tonic firing of TC neurons seems to be mainly based on the block of HCN channels.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is possible that Nav1.5 was also inhibited. Kirchhof and colleagues showed that selective activation of the brain-type Na + channel Nav1.3 can increase cardiac contractility without provoking arrhythmia [ 7 ]. In this context, our data suggest that Nav1.3 is a feasible target of the positive inotropic agent HNO.…”
Section: Discussionmentioning
confidence: 99%
“…Nav1.1, Nav1.3, and Nav1.6 are localized to t-tubules or near t-tubule openings [ 5 , 6 ]. Kirchhof et al reported that a peptide that activates Nav1.3 and Nav1.6 can induce positive inotropy without provoking arrhythmias [ 7 ]. We have previously demonstrated that Nav1.5 and brain-type subunits are differentially inhibited Na + channel inhibitors including local anesthetics [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, there is evidence that augmentation of Na + influx through nNa V in WT murine hearts may be potentially inotropic by increasing Ca 2+ transient amplitude (Kirchhof et al . ; Radwanski et al . ).…”
Section: The Interplay Between Sodium and Calciummentioning
confidence: 99%